Multimodal Aposematic Signals and Their Emerging Role in Mate Attraction - Rojas, Bibiana; Burdfield-Steel, Emily; De Pasqual, Chiara; Gordon, Swanne; Hernández, Linda; Mappes, Johanna; Nokelainen, Ossi; Rönkä, Katja; Lindstedt, Carita (Frontiers in Ecology and Evolution, 2018)
Chemically defended animals often display conspicuous colour patterns that predators learn to associate with their unprofitability and subsequently avoid. Such animals (i.e. aposematic), deter predators by stimulating their visual and chemical sensory channels. Hence, aposematism is considered to be ‘multimodal’. The evolution of warning signals (and to a lesser degree their accompanying chemical defences) is fundamentally linked to natural selection by predators. Lately, however, increasing evidence also points to a role of sexual selection shaping warning signal evolution. One of the species in which this has been shown is the wood tiger moth, Arctia plantaginis, which we here put forward as a promising model to investigate multimodality in aposematic and sexual signalling. A. plantaginis is an aposematic diurnal moth which exhibits sexually dimorphic colouration as well as sex-limited polymorphism in part of its range. The anti-predator function of its colouration and, more recently, its chemical defences (even when experimentally decoupled from the visual signals) have been well-demonstrated. Interestingly, recent studies have revealed differences between the two male morphs in mating success, suggesting a role of colouration in mate choice or attraction, and providing a possible explanation for its sexual dimorphism in colouration. Here, we: (1) review the lines of evidence showing the role of predation pressure and sexual selection in the evolution of multimodal aposematic signals in general, and in the wood tiger moth in particular; (2) establish gaps in current research linking sexual selection and predation as selective pressures on aposematic signals by reviewing a sample of the literature published in the last 30 years; (3) highlight the need of identifying suitable systems to address simultaneously the effect of natural and sexual selection on multimodal aposematic signals; and (4) propose directions for future research to test how aposematic signals can evolve under natural and sexual selection.